2020
DOI: 10.1007/s42452-020-03425-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and fracture parameters of ultra high performance steel fiber reinforced concrete composites made with extremely low water per binder ratios

Abstract: This study examines the effects of high-volume micro-steel fibers (MSF) content on the mechanical properties, fracture parameters, and ductility of ultra-high performance fiber reinforced concrete (UHPFRCs). The MSFs used in this experiment had an aspect ratio of 37.5 with average length of 6 mm. The investigated parameters include very low water/binder (w/b) ratio and fiber content. Sixteen UHPFRC mixes were examined, eight mixes were made with w/b of 0.12 and eight fiber contents (0%, 1%, 1.5%, 2%, 2.5%, 3%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…This may be attributed to the chemical and physical changes due to temperature and humidity effects on potential for the stress transfer. Additionally, the modulus of elasticity for the water-cured UHPFRC at 1150 kg/m 3 binder content achieved in this study was 41.15 GPa, whereas the modulus of elasticity for the same MSF content, w/b, and curing condition at 1175 kg/m 3 binder content achieved by Qadir et al [ 28 ] was nearly 40 MPa.…”
Section: Resultsmentioning
confidence: 41%
See 4 more Smart Citations
“…This may be attributed to the chemical and physical changes due to temperature and humidity effects on potential for the stress transfer. Additionally, the modulus of elasticity for the water-cured UHPFRC at 1150 kg/m 3 binder content achieved in this study was 41.15 GPa, whereas the modulus of elasticity for the same MSF content, w/b, and curing condition at 1175 kg/m 3 binder content achieved by Qadir et al [ 28 ] was nearly 40 MPa.…”
Section: Resultsmentioning
confidence: 41%
“…In addition, the reason for the necessary increasing of SP with a greater increase in binder after 1150 kg/m 3 may be attributed to the better dispersion of micro silica particles at 1200 kg/m 3 of binder used. It was also reported that for the production of UHPC with 2% MSF and 1175 kg/m 3 binder content at 0.12 w/b the SP demand was nearly 70 kg/m 3 [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations